2012
DOI: 10.3819/ccbr.2012.7002
|View full text |Cite
|
Sign up to set email alerts
|

Neurophysiological Studies of Learning and Memory in Pigeons

Abstract: The literature on the neural basis of learning and memory is replete with studies using rats and monkey, but hardly any using pigeons. This is odd because so much of what we know about animal behavior comes from studies with pigeons. The unwillingness to use pigeons in neural studies of learning and memory probably stems from two factors, one that the avian brain is seen as radically different from the mammalian brain and as such can contribute little to its understanding, and the other that the behavior of pi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…Both the NCL and the PFC show great similarities in anatomical, neurochemical, electrophysiological, and behavioral characteristics (Güntürkün, 2005a, 2005b), as well as a comparable receptor architecture (Herold et al, 2011). A laminar cortex as in mammals is not required to support higher cognitive processes (for a review see Colombo & Scarf, 2012). In this study, we further demonstrated this with respect to reward processing.…”
Section: Discussionmentioning
confidence: 99%
“…Both the NCL and the PFC show great similarities in anatomical, neurochemical, electrophysiological, and behavioral characteristics (Güntürkün, 2005a, 2005b), as well as a comparable receptor architecture (Herold et al, 2011). A laminar cortex as in mammals is not required to support higher cognitive processes (for a review see Colombo & Scarf, 2012). In this study, we further demonstrated this with respect to reward processing.…”
Section: Discussionmentioning
confidence: 99%
“…Although avian HF interneurons cannot be directly compared to the types of interneurons found in the mammalian hippocampus, they may share comparable modulatory capabilities. Neurons of the avian HF display spike morphology/firing rate profiles similar to those in the mammalian hippocampus (Siegel et al, ; Hough and Bingman, ; Colombo and Scarf, ). For example, neurons of the V‐complex fire at rates similar to CA1 neurons and avian DL neurons display firing patterns resembling the cells of the subiculum.…”
Section: Anatomy Of the Avian Hfmentioning
confidence: 97%
“…Indeed, there is a long history of research examining the learning and cognitive abilities of pigeons (Colombo & Scarf, 2012; Cook, Katz, & Blaisdell, 2012; Herrnstein, Loveland & Cable, 1976; Wasserman, Kiedinger & Bhatt, 1988; Wright, 1997), including memory for items recently presented in a sequence (Cook & Blaisdell, 2006). …”
Section: Serial Pattern Learning In Pigeonsmentioning
confidence: 99%